Nghiên cứu và chế tạo máy bán hàng tự động tại Việt Nam - Nguyen, Ngọc Phương (Journal of Technical Education Science, 2007)
This article presents the outline of reseaching and manufacturing the vending ma- chines in Viet Nam. Now, this problem is new and necessary for socioeconomic needs. The machines are manufactured with Vietnam’s equipments and work well in many dif- ference conditions